XML views, part III: An UML based design methodology for XML views - Chang, Elizabeth; Rajugan, R.; Dillon, Tharam S.; Feng, L. (INSTICC - Institute for Systems and Technologies of Information, Control and Communication, 2005)
Object-Oriented (OO) conceptual models have the power in describing and modelling real-world data semantics and their inter-relationships in a form that is precise and comprehensible to users. Today UML has established itself as the language of choice for modelling complex enterprises information systems (EIS) using OO techniques. Conversely, the eXtensible Markup Language (XML) is fast emerging as the dominant standard for storing, describing and interchanging data among various enterprises systems and databases. With the introduction of XML Schema, which provides rich facilities for constraining and defining XML content, XML provides the ideal platform and the flexibility for capturing and representing complex enterprise data formats. Yet, UML provides insufficient modelling constructs for utilising XML schema based data description and constraints, while XML Schema lacks the ability to provide higher levels of abstraction (such as conceptual models) that are easily understood by humans. Therefore to enable efficient business application development of large-scale enterprise systems, we need UML like models with rich XML schema like semantics. To address such issue, in this paper, we proposed a generic, semantically rich view mechanism to conceptually model and design (using UML) XML domains to support data modelling of complex domains such as data warehousing and e-commerce systems. Our approach is based on UML and UML stereotypes to design and transform XML views.